2022
DOI: 10.1186/s13071-022-05542-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic insecticide resistance status of the Culex pipiens complex: a European perspective

Abstract: Background The common house mosquito Culex pipiens is known to be a major vector for West Nile virus. In order to decrease risks of West Nile virus outbreaks in Europe, insecticides and the bio-larvicide Bacillus thuringiensis israelensis (Bti) are commonly used for vector control. Alarmingly, insecticide resistance has been reported in Cx. pipiens populations from Southern Europe and several countries neighbouring Europe. For Central and Northern Europe, however, the phenotypic insecticide res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Emerging insecticide resistance remains one of the major challenges in mosquito control [ 42 , 43 , 44 , 45 ]. Laccase 2 and tyrosine hydroxylase were included in a list of promising genetic targets for RNAi-based mosquito control to overcome insecticide-resistant populations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging insecticide resistance remains one of the major challenges in mosquito control [ 42 , 43 , 44 , 45 ]. Laccase 2 and tyrosine hydroxylase were included in a list of promising genetic targets for RNAi-based mosquito control to overcome insecticide-resistant populations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified various pesticides in the mosquito crops. Recently, the insecticide resistance of Belgian C. pipiens have been investigated [ 39 ]. In this study, the authors showed that C. pipiens developed resistance against pyrethroids deltamethrin and permethrin, and possibly against carbamate Bendiocarb.…”
Section: Discussionmentioning
confidence: 99%
“…This might, in turn, open the potential for the registry of second-generation ATSBs that include RNAi yeast as an active ingredient. RNAi yeast ATSBs could enhance existing ATSB technology as a mosquito-specific next-generation ATSB, the use of which could help combat insecticide resistance, a growing problem which must be addressed by the development of new interventions [24][25][26]. The specificity of the Sh.463 shRNA insecticide for mosquitoes, as illustrated by the observed lack of impact of this insecticide on other insects [4], makes it an eco-friendly alternative to broad-based insecticides.…”
Section: Discussionmentioning
confidence: 99%